Congestion location detection: Methodology, algorithm, and performance - Shao Liu; Mung Chiang; Jourdain, M.; Jin Li (2009 17th International Workshop on Quality of Service, 2009)
We address the following question in this study: Can a network application detect not only the occurrence, but also the location of congestion? Answering this question will not only help the diagnostic of network failure and monitor server's QoS, but also help developers to engineer transport protocols with more desirable congestion avoidance behavior. The paper answers this question through new analytic results on the two underlying technical difficulties: 1) synchronization effects of loss and delay in TCP, and 2) distributed hypothesis testing using only local loss and delay data. We present a practical congestion location detection (CLD) algorithm that effectively allows an end host to distributively detect whether congestion happens in the local access link or in more remote links. We validate the effectiveness of CLD algorithm with extensive experiments.